Separate cis-regulatory elements confer expression of phosphoenolpyruvate carboxykinase (GTP) gene in different cell lines. - Benvenisty, N (1989)
The gene encoding cytosolic phosphoenolpyruvate carboxykinase (GTP) [PEPCK; GTP:oxaloacetate carboxy-lyase (transphosphorylating), EC 4.1.1.32], a key enzyme in gluconeogenesis and glyceroneogenesis, is expressed in tissues that arise from different embryonal origins: the gluconeogenic liver arises from endoderm, whereas the gluconeogenic kidney cortex and glyceroneogenic adipose tissue arise from the mesoderm. To identify the cis-regulatory elements conferring the differential gene expression, PEPCK chimeric genes were transfected into two rat hepatoma cell lines (H4IIEC3 and HTC-M1.1) and mouse adipocytes (3T3F442A), which express the endogenous gene, and into myoblasts and preadipocytes, which do not express it. The results demonstrate that 597 base pairs of the 5' flanking region of the PEPCK gene are sufficient to confer cell-specific gene expression in the PEPCK-expressing hepatoma cells and adipocytes. However, different elements within this 597-base-pair region enhance the gene expression in the hepatoma cells (endoderm) and adipocytes (mesoderm). In the hepatocytes, expression is conferred by two elements--one 5' of position -362 and the other 3' of position -98 with respect to the transcription start site. The region in between these two elements (from -362 to -98), which seems to inhibit the gene expression in the hepatocytes, confers enhanced expression in the adipocytes. Moreover, the distal positive regulatory element of the hepatocytes seems to be orientation and PEPCK promoter dependent. In contrast, the positive regulatory element of the adipocytes seems to act as a more typical enhancer. These results suggest that separate cis-regulatory elements confer cell-specific expression of the PEPCK gene.